2021
DOI: 10.3390/ijms22020550
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-23b/27b/24-1 Cluster Impairs Glucose Tolerance via Glycolysis Pathway in Mice

Abstract: Alterations in miRNAs are associated with many metabolic disorders, such as type 2 diabetes (T2DM). The miR-23b/27b/24-1 cluster contains miR-23b, miR-27b, and miR-24-1, which are located within 881 bp on chromosome 9. Studies examining the roles of miR-23b, miR-27b, and miR-24-1 have demonstrated their multifaceted functions in variable metabolic disorders. However, their joint roles in metabolism in vivo remain elusive. To investigate this subject, we constructed miR-23b/27b/24-1 cluster knockout (KO) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…These miRNAs are highly expressed in vascularized tissues [60]. In addition, miR-27b was shown to target the NOTCH ligand Delta-like ligand 4 (Dll4) [55]. To note, the NOTCH pathway was enriched in our pathway analysis.…”
Section: Analysis Of Single Snpsmentioning
confidence: 89%
See 1 more Smart Citation
“…These miRNAs are highly expressed in vascularized tissues [60]. In addition, miR-27b was shown to target the NOTCH ligand Delta-like ligand 4 (Dll4) [55]. To note, the NOTCH pathway was enriched in our pathway analysis.…”
Section: Analysis Of Single Snpsmentioning
confidence: 89%
“…The role of these miRNAs has not been fully elucidated, however studies examining the roles of miR-23b, miR-27b and miR-24-1 have demonstrated their multiple functions, ranging from metabolic disorders to proliferation and development disorders [55][56][57][58][59][60]. These miRNAs are highly expressed in vascularized tissues [60].…”
Section: Analysis Of Single Snpsmentioning
confidence: 99%
“…Overexpression of miR-27b was found to inhibit NRF2 activation, a master regulator of antioxidant response [54], and suppress NFKB activation [55]. Furthermore, mir-27b upregulation has been associated with the onset of retinopathy [56], while its downregulation has been implicated in glucose tolerance impairment [57] and nephropathy [58]. The upregulation of mir-148a has been consistently found in T1D patients [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Small endogenous regulatory RNAs, also known as short-strand ribonucleic acid microRNAs (miRNAs), are critical posttranscriptional regulators of gene expression and were first identified in C. elegans [19][20][21]. ere are many kinds of miRNAs, among which miRNA-23b belongs to miR-23b/27b/24-1 cluster [22]. miR-23b possessed regulatory roles, especially in the development of cancer and autonomic immune diseases [23].…”
Section: Introductionmentioning
confidence: 99%